Glitazone Treatment and Incidence of Parkinson's Disease among People with Diabetes: A Retrospective Cohort Study - Brauer,R; Bhaskaran,K; Chaturvedi,N; Dexter,DT; Smeeth,L; Douglas,I (PLOS Medicine, 2015)
BackgroundRecent in vitro and animal experiments suggest that peroxisome proliferation-activatedreceptor gamma (PPAR) agonist medications, such as antidiabetic glitazone (GTZ) drugs,are neuroprotective in models of Parkinson’s disease (PD). These findings have not beentested in humans. We hypothesized that individuals prescribed GTZ drugs would have alower incidence of PD compared to individuals prescribed other treatments for diabetes.Methods and FindingsUsing primary care data from the United Kingdom Clinical Practice Research Datalink(CPRD), we conducted a retrospective cohort study in which individuals with diabetes whowere newly prescribed GTZ (GTZ-exposed group) were matched by age, sex, practice,and diabetes treatment stage with up to five individuals prescribed other diabetes treatments(other antidiabetic drug-exposed group). Patients were followed up from 1999 untilthe first recording of a PD diagnosis, end of observation in the database, or end of the study(1 August 2013). An incidence rate ratio (IRR) was calculated using conditional Poissonregression, adjusted for possible confounders. 44,597 GTZ exposed individuals werematched to 120,373 other antidiabetic users. 175 GTZ-exposed individuals were diagnosedwith PD compared to 517 individuals in the other antidiabetic drug-exposed group. The incidencerate (IR) of PD in the GTZ-exposed group was 6.4 per 10,000 patient years comparedwith 8.8 per 10,000 patient years in those prescribed other antidiabetic treatments(IRR 0.72, 95% confidence interval [CI] 0.60–0.87). Adjustments for potential confoundingvariables, including smoking, other medications, head injury, and disease severity, had nomaterial impact (fully adjusted IRR 0.75, 0.59–0.94). The risk was reduced in those with currentGTZ prescriptions (current GTZ-exposed IRR 0.59, 0.46–0.77) but not reduced amongthose with past prescriptions (past GTZ-exposed IRR 0.85, 0.65–1.10). Our study only included patients with diabetes